EVALUASI PROSES PEMBAYARAN KLAIM ASPAN OTO PADA PT. ASURANSI PURNA ARTHANUGRAHA CABANG PONTIANAK - B51110003, YOSEF HENDRA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Thesis entitled "Evaluation of the claims payment process Aspan OTO at PT. Purna Insurance Arthanugraha Pontianak Branch "featuring two problems that the Claim Payment Process Aspan How OTO at PT. Purna Insurance Artanugraha Pontianak Branch and Any Obstacles Encountered in Claims Payment Process Aspan OTO at PT. Purna Insurance Artanugraha Pontianak Branch. The purpose of this study was to determine the systems and procedures for the payment of claims Aspan OTO at PT. Purna Insurance Artanugraha Pontianak Branch as well as to determine any constraints that become an obstacle in the claim process Aspan OTO at PT. Purna Insurance Artanugraha Pontianak Branch. The method used is a Qualitative Method by means of Descriptive Analysis. The author is collecting data through interviews, documentary studies and questionnaires. The results of the formulation of the issue under study is presented in Chapter 4 is the analysis and discussion of the evaluation form and describe the claims payment procedures according to the results of interviews and questionnaires conducted. As well as sums and presented in chapter 5. Keywords: Aspan OTO, OTO Aspan Evaluation of Insurance Claims, Insurance Procedure.